dampak fluktuasi harga kedelai impor dan upah tenaga kerja terhadap jumlah produksi tempe pada UD. edwin di desa teja kecamatan pamekasan kabupaten pamekasan - Musyarrofah, Musyarrofah; Ningsih, Kustiawati; Sustiyana, Sustiyana (JURNAL AGROSAINS : Karya Kreatif dan Inovatif, 2024)
Tempeh industry is an industry that uses raw materials such as soybeans and yeast. This industry is mostly managed by Indonesian people, both in rural and urban areas. The tempeh industry often experiences the problem of fluctuations in the price of soybeans which are used as its main raw material, the price tends to rise, while the selling price of tempeh is difficult to increase. This study aims to describe the impact of fluctuations in imported soybean prices and labor wages on the amount of tempe production at UD. Edwin 2018-2021. The research method uses descriptive qualitative and takes samples using the purposive sampling method because the research informants are determined deliberately. The data analysis method uses multiple linear regression data analysis methods to determine the causal or causal relationship between the independent variables and the dependent variable. The results of this study indicate that the independent variable has an effect of 92.2% on the dependent variable, meaning that the price of imported soybeans and labor wages together affect the amount of tempe production. The higher the price of imported soybeans, the lower the amount of tempe production, conversely, the lower the price of imported soybeans, the greater the amount of tempeh production.